High Doses of Caffeine during the Peripubertal Period in the Rat Impair the Growth and Function of the Testis - Minji Park; Yuri Choi; Hyeonhae Choi; Ju-Yearn Yim; Jaesook Roh (International Journal of Endocrinology)
Prenatal caffeine exposure adversely affects the development of the reproductive organs of male rat offspring. Thus, it is conceivable that peripubertal caffeine exposure would also influence physiologic gonadal changes and function during this critical period for sexual maturation. This study investigated the impact of high doses of caffeine on the testes of prepubertal male rats. A total of 45 immature male rats were divided randomly into three groups: a control group and 2 groups fed 120 and 180 mg/kg/day of caffeine, respectively, via the stomach for 4 weeks. Caffeine caused a significant decrease in body weight gain, accompanied by proportional decreases in lean body mass and body fat. The caffeine-fed animals had smaller and lighter testes than those of the control that were accompanied by negative influences on the histologic parameters of the testes. In addition, stimulated-testosterone ex vivo production was reduced in Leydig cells retrieved from the caffeine-fed animals. Our results demonstrate that peripubertal caffeine consumption can interfere with the maturation and function of the testis, possibly by interrupting endogenous testosterone secretion and reducing the sensitivity of Leydig cells to gonadotrophic stimulation. In addition, we confirmed that pubertal administration of caffeine reduced testis growth and altered testis histomorphology.